Analysis Questioning Skills of Biology Education Student Based on Different Academic Abilities and the Correlation With Metacognitive Skills - Kusuma, Anindita Suliya Hangesti Mandra; Rasmi, Dewa Ayu Citra; Artayasa, I Putu; Ilhamdi, M Liwa; Setiawan, Heru (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2025)
The aim of this research is to determine the questioning skills of Biology Education students based on different academic abilities and their correlation with metacognitive skills. This study employs a mixed methods design. The sample in the study consists of biology education students from the Faculty of Teacher Training and Education, University of Mataram. The instruments used in this research include the Questioning Skills Instrument and an Achievement test to measure metacognitive skills. The data analysis used in this research includes descriptive and inferential statistical analysis (correlation and regression). The results of the qualitative analysis using descriptive statistics show that the questioning skills of students with low academic performance mostly remain at level C2 (comprehension questions), comprising 58% of the questions, and C1 (recall questions), comprising 38% of the questions. A small proportion were able to formulate questions at level C3 (application questions), comprising 15% of the questions, and only 1% were able to formulate questions at level C4 (analysis questions). For students with high academic performance, most of the questioning skills were at level C3 (application questions), comprising 36.67% of the questions, and C2 (comprehension questions), comprising 35.56% of the questions. Additionally, 18.89% of the questions reached level C4 (analysis questions), and 3.33% reached level C5 (evaluation questions). Only a small proportion formulated questions at level C1 (recall questions), comprising 1.11% of the questions. The analysis of the relationship between questioning skills and metacognitive skills indicates that there is a relationship between students' questioning skills and metacognitive skills when using the Reading Concept Mapping-Reciprocal Teaching (ReMap-RT) learning model, with a correlation coefficient of 0.868 (high). The direction of the relationship between questioning skills and metacognitive skills is positive. The coefficient of determination (r²) is 0.754, which explains that the variability in students' metacognitive skills is determined by 75.4% of the questioning skills. The significance value of this regression is also used to determine whether the regression equation can be used for prediction. If the significance value of the regression is less than the determined significance level, then the regression equation can be used for prediction. Based on the analysis results, the regression significance value is 0.00 < 0.05, so it can be concluded that the regression equation can also be used for prediction. The regression equation for the relationship between questioning skills and metacognitive skills of students using the Reading Concept Mapping-Reciprocal Teaching (ReMap-RT) learning model is Ŷ = 38.791 + 3.185X.